Does man live forever? The evidence and testimony of Scripture concerning the soul in life and in death ; eternal punishment ; restorationalism - Grant, Frederick William, 1834-1902; Darby, John Nelson, 1800-1882 (London, UK Pickering and Inglis)
Contents : The doctrine of the soul in life and death, by F.W.G.; Brief scriptural evidence on the doctrine of eternal punishment for plain people, new ed., by J.N.D.; The testimony of Scripture in contrast with the doctrines of restorationism (author unknown).
Brethren writers.
Keywords: Future state -- biblical teaching